PREVENTING FALSE AND MANIPULATIVE ADVERTISING IN SOCIAL NETWORKS - Raimova, Nargiza; To‘ychiyeva, Bahora (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In the contemporary digital landscape, the proliferation of social networks has fundamentally transformed the dynamics of advertising, significantly enhancing both its reach and impact. With billions of users engaging daily, these platforms serve as formidable channels for marketers aiming to influence consumer behavior. However, this unprecedented access also paves the way for misinformation and manipulative practices, which can distort consumer perceptions and undermine trust in legitimate advertisements. Consequently, the need to scrutinize the ethical implications of advertising strategies in social networks has become paramount.